PENGARUH PENYERTAAN MODAL PEMERINTAH KOTA DAN PEMERINTAH PROVINSI TERHADAP KINERJA KEUANGAN PERUSAHAAN DAERAH AIR MINUM TIRTA KENCANA SAMARINDA - -, MUHAMAD YANI (EKONOMIA, 2017)
This study aims to determine the effect of Government capital inclusion the City and Provincial Government on the financial performance ratio of the Regional Water Company Tirta Kencana Samarinda. This study uses primary data is direct interviews and secondary data published by the Regional Water Company (PDAM) Tirta Kencana 2010-2015. It is analyzed by ratios of the company's financial performance. Results of analysis showed that this increased financial performance significantly in the years 2010 to 2014 except 2015 decreased performance. This performance decrease occurs one of them caused by the costs incurred to produce, process, and distribute it to customers, so the impact of expenditures that are too large lead to a loss in 2015.